Effect of Intravenous Magnesium Sulphate Added to Paracetamol Lignocaine Regimen on Hemodynamic Response to Laryngoscopy and Intubation: A Randomized Double-Blind Clinical Study - Lole, Nikita Vijay; Kanase, Naseema; Sachin; Patwardhan, Mugdha (International Journal of Medical Research, 2025)
Background: Laryngoscopy and intubation cause marked sympathetic activation with rises in heart rate and blood pressure. Paracetamol and lignocaine provide limited control, especially of arterial pressure. Magnesium sulphate, with sympatholytic and calcium-antagonist actions, may improve stability. This study evaluates whether adding intravenous magnesium enhances attenuation of these hemodynamic responses. Methods: This randomized, double-blind comparative study included 60 ASA I, II patients aged 20-50 years undergoing elective surgery under general anaesthesia. Participants were allocated to two groups: Group PML received intravenous paracetamol, magnesium sulphate (50 mg/kg), and lignocaine; Group PL received paracetamol, placebo saline, and lignocaine. Hemodynamic parameters heart rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were recorded at baseline, post-induction, immediately after intubation, and at 1, 3, 5, 10, and 15 minutes. Results: Baseline characteristics were comparable between groups. Heart rate responses remained similar at most time points, with Group PL showing significantly higher values at 15 minutes (p <0.05). SBP, DBP, and MAP were significantly lower in Group PML at all post-intubation intervals (p <0.01), indicating superior attenuation of pressor responses. Oxygen saturation remained stable in both groups. Conclusion: The addition of magnesium sulphate to a paracetamol lignocaine regimen effectively blunts the hypertensive response to laryngoscopy and intubation, offering enhanced cardiovascular stability without compromising safety.